Is It Possible to Reconstruct the Theory of Adult Education by the Integration of the Humanist, Critical, and Postmodern Perspectives? - Sánchez-Domenech, Iluminada (2017)
This essay tries to answer the following question: is it possible the integration of apparently excluding or contradictory conceptions in the construction of the theory of adult education (AE)? We assume that there is a need for the professionals in charge of adult education to have a theoretical framework of reference that guides them in their practice, and helps them in the development of their own identity as professionals. However, the contributions of different schools of thought have tended to be contradictory or mutually excluding, hindering the development of the theory. Following the objectives of knowledge of the theory of education, we analyze some key concepts that have centered the discussions on the field of study of the AE over the past four decades. For this analysis, we create a dialectical interaction between the humanistic, critical, and postmoderm educational thoughts through some of their most representative authors and around those concepts. In this way, it is shown how it is possible to reconsider the AE from an integrative perspective, although with conceptual and ideological nuances that, far from being an obstacle, enrich the theory and reflect the diversity of the same social agents.